SCATTERING OF A SIMPLE INDIVIDUAL RADAR PULSE IN RARIFIED MEDIUM - S. F. Kolomiets (Научный вестник МГТУ ГА, 2016)
The experimental data obtained in different years and by different scientific groups in rains (as rarified medium) are discussed in the article. It is shown that the results of such measurements are not complying with well-known Kerr-Rice model widely used for modeling backscattering of rarified medium. Short analysis of reasons for this is presented